Benefits to decomposition rates when using digestate as compost co-feedstock: Part II – Focus on microbial community dynamics. (October 2017) - Arab, Golnaz; Razaviarani, Vahid; Sheng, Zhiya; Liu, Yang; McCartney, Daryl
Highlights: Higher microbial diversity observed when digestate added to fresh feedstock. Actinomyces sp. was more abundant when digestate added. Two fungi, Galactomyces and Pichia, predominate when digestate added. Chaetomium and Acremonium possibly increased OM degradation when digestate added. RDA analysis correlated microbial dynamics to environmental factors. Abstract: Linkage between composting reactor performance and microbial community dynamics was investigated during co-composting of digestate and fresh feedstock (organic fraction of municipal solid waste) using 25 L reactors. Previously, the relationship between composting performance and various physicochemical parameters were reported in Part I of the study (Arab and McCartney, 2017). Three digestate to fresh feedstock ratios (0, 40, and 100%; wet weight basis) were selected for analysis of microbial community dynamics. The 40% ratio was selected because it was found to perform the best (Arab and McCartney, 2017). Illumina sequencing results revealed that the reactor with a greater composting performance (higher organic matter degradation and higher heat generation; 40% ratio) was associated with higher microbial diversity. Two specific bacterial orders that might result in higher performance were Thermoactinomycetaceae and Actinomycetales with a higher sequence abundance during thermophilic composting phase and during the maturing composting phase, respectively. Galactomyces, Pichia, Chaetomium, and Acremonium were the four fungal genera that are probably also involved in higher organic matter degradation in the reactor with better performance. The redundancy analysis (RDA) biplot indicated that among the studied environmental variables, temperature, total ammonia nitrogen and nitrate concentration accounted for much of the major shifts in microbial sequence abundance during the co-composting process.